Backbone.js cookbook : over 80 recipes for creating outstanding web applications with Backbone.js, leveraging MVC, and REST architecture principles /: over 80 recipes for creating outstanding web applications with Backbone.js, leveraging MVC, and REST architecture principles. (2013) - Unknown
No abstract available